A PREPARATION OF DRAMA PERFORMANCE BY CREATING VISUAL SYMBOL RESPONSE AMID THE COVID-19 PANDEMIC - Munikahi Purba; Rita Inderawati (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2021)
This study aimed to elaborate on the students’ creativity in responding to literary works, in this case, a poem entitled Beowulf by utilizing visual symbols. The population of this research students from the 4th semester of English education in Sriwijaya University in the academic year 2020/2021 consists of 73 students. The researcher used the purposive sampling method. There were 34 students chosen as samples. The instruments of the research were test and documentation of their Visual Symbol Response which were analyzed by using Rubric for Creativity. The result showed students can appreciate literature using visual symbols. These symbols can help students visualize the words written in literary works so as to form an interesting performance. On the other hand, the students have been able to elaborate on critical thinking and also their creativity. The students were generally not at the degree of "imitative" in any way. The vast majority of students were "creative," but none of them were "very creative." Critical thinking may aid readers in discovering the deeper meaning of a piece of prose or poem, as well as allowing them to see the other side or what lies behind it. The students enjoy their creativity as they have strived to create visual symbols to be interesting videos as the early effort to prepare virtual drama performance. AbstrakPenelitian ini bertujuan untuk mengelaborasi kreativitas siswa dalam merespon karya sastra, dalam hal ini puisi berjudul Beowulf dengan memanfaatkan simbol-simbol visual. Populasi penelitian ini adalah mahasiswa semester 4 pendidikan bahasa Inggris di Universitas Sriwijaya tahun ajaran 2020/2021 berjumlah 73 mahasiswa. Peneliti menggunakan metode purposive sampling. Ada 34 siswa yang dipilih sebagai sampel. Instrumen penelitian berupa tes dan dokumentasi Respon Simbol Visual yang dianalisis menggunakan Rubrik Kreativitas. Hasil penelitian menunjukkan siswa dapat mengapresiasi karya sastra dengan menggunakan simbol-simbol visual. Simbol-simbol tersebut dapat membantu siswa memvisualisasikan kata-kata yang tertulis dalam karya sastra sehingga membentuk suatu pertunjukan yang menarik. Di sisi lain, siswa telah mampu mengelaborasi pemikiran kritis dan juga kreativitasnya. Para siswa umumnya tidak pada tingkat "meniru" dengan cara apa pun. Sebagian besar siswa adalah "kreatif", tetapi tidak satu pun dari mereka yang "sangat kreatif". Berpikir kritis dapat membantu pembaca dalam menemukan makna yang lebih dalam dari sebuah prosa atau puisi, serta memungkinkan mereka untuk melihat sisi lain atau apa yang ada di baliknya. Para siswa menikmati kreativitas mereka karena mereka telah berusaha untuk membuat simbol visual menjadi video yang menarik sebagai upaya awal untuk mempersiapkan pertunjukan dramavirtual.